The research that resulted in the book about the Collection of traditional children's toys of the Ethnographic Museum in Zagreb - Biškupić-Bašić, Iris (Array, 2019)
On the occasion of the 100th anniversary of the Ethnographic Museum in Zagreb the author provides a biref overview of the origins and the preservation of the Collection of Traditional Children’s Toys from 1919 to date. Based on long-term research and processing of the collections, as well as the recently released publication about traditional children’s toys, the text presents the development of the Collection with a special reference to several centuries of toy making in some Croatian villages. The paper focuses on the regions of Prigorje, Zagorje and the Dalmatian Hinterland, localities in Croatia in which this activity has developed as home-based businesses that brought economic gains through manufacturing and sale of children’s toys from the 19th century to this day. The text has been supported by documents and data collected during field research while co-operating with narrators, children’s toys makers and through the study of archival and library collections, in order to preserve the heritage for future generations.